2020
DOI: 10.1021/acs.estlett.9b00789
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Efficacy-Risk of the Widely Used Chiral Glufosinate: Switch from the Racemate to the Single Enantiomer?

Abstract: The chirality of pesticides has emerged as an important issue in pesticide design and applications because enantiomers can differ greatly in their environmental fate and risk. Despite the increasing concern over the unintended effects of inactive or less effective enantiomers, massive amounts of chiral pesticides are applied as racemic mixtures. As a potential substitute for glyphosate, the market of glufosinate is expected to grow rapidly. However, very little information is available on its enantioselective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…A recent study has shown that L-phosphinothricin was favored in an efficacy-risk assessment by better inhibiting weed growth and less early life toxicity to offtarget organisms compared to the racemic mixture. 45 Since glufosinate and its metabolites are highly water soluble, they neither volatilize nor accumulate in the food chain (Table 1). 1 Glufosinate does not remain in the soil because it is rapidly degraded by soil bacteria, resulting in no residual activity nor crop rotation restrictions.…”
Section: Glufosinate In the Ecosystemmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has shown that L-phosphinothricin was favored in an efficacy-risk assessment by better inhibiting weed growth and less early life toxicity to offtarget organisms compared to the racemic mixture. 45 Since glufosinate and its metabolites are highly water soluble, they neither volatilize nor accumulate in the food chain (Table 1). 1 Glufosinate does not remain in the soil because it is rapidly degraded by soil bacteria, resulting in no residual activity nor crop rotation restrictions.…”
Section: Glufosinate In the Ecosystemmentioning
confidence: 99%
“…Alternatively, switching from the racemate to the single enantiomer could reduce by half the total amount of glufosinate applied to the environment. A recent study has shown that L‐phosphinothricin was favored in an efficacy‐risk assessment by better inhibiting weed growth and less early life toxicity to off‐target organisms compared to the racemic mixture 45 . Since glufosinate and its metabolites are highly water soluble, they neither volatilize nor accumulate in the food chain (Table 1).…”
Section: Glufosinate In the Ecosystemmentioning
confidence: 99%
“…The commercial product is a racemic mixture of the active, pure L-glufosinate which is identical to phosphinothricin and the inactive D-glufosinate (Copping, Duke, 2007). Efforts are being made to economically produce the L-enantiomer, the use of which would be advantageous to reduce crop injury and for potential toxicological reasons (Takano, Dayan, 2020;Yue et al, 2020). There are numerous other natural GS inhibitors that are not commercialized as herbicides (Lydon, Duke, 1999), perhaps because of high cost and/or inadequate physicochemical properties.…”
Section: Used To Identify New Herbicide Targetsmentioning
confidence: 99%
“…2.3 | Synthesis of the noscapine derivative chiral stationary phase 2.3.1 | Synthesis of N-nornoscapine; (3S)-6,7-dimethoxy-3-[(5R)-4-methoxy-5,6,7,8-tetrahydro- [1,3]dioxolo[4,5-g]isoquinlin-5-yl]-2-benzofuran-1(3H)-one (2)…”
Section: Instrumentationmentioning
confidence: 99%
“…Enantioseparation is of great importance in both pharmaceutical and biological industries 1 because in most cases, single enantiomers are mainly more active, selective, preferable, and less toxic as compared to racemates. 2,3 However, it is noteworthy that the development of a chiral pharmaceutical ingredient in a racemic form can be more affordable for the pharmaceutical industry. 4 Resolution of enantiomers is achievable using different techniques such as crystallization, [5][6][7] capillary electrophoresis (CE), [8][9][10] and chromatography.…”
Section: Introductionmentioning
confidence: 99%